2016
DOI: 10.1681/asn.2016040412
|View full text |Cite
|
Sign up to set email alerts
|

Complications of the Arteriovenous Fistula: A Systematic Review

Abstract: The implementation of patient-centered care requires an individualized approach to hemodialysis vascular access, on the basis of each patient's unique balance of risks and benefits. This systematic review aimed to summarize current literature on fistula risks, including rates of complications, to assist with patient-centered decision making. We searched Medline from 2000 to 2014 for English-language studies with prospectively captured data on ≥100 fistulas. We assessed study quality and extracted data on study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(117 citation statements)
references
References 88 publications
1
102
0
14
Order By: Relevance
“…However, the high flow rates needed for haemodialysis that they provide are not needed for LA and AV fistulas can give rise to problems such as strictures at the anastomosis [23]. Infection, aneurysm, vascular steal and thrombosis are well-described in the context of AV fistulas used for haemodialysis [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the high flow rates needed for haemodialysis that they provide are not needed for LA and AV fistulas can give rise to problems such as strictures at the anastomosis [23]. Infection, aneurysm, vascular steal and thrombosis are well-described in the context of AV fistulas used for haemodialysis [24].…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Thrombosis and stenosis are closed related with AVF, and they will increase patients’ economic burden and lower their quality of life, which are the main causes for AVF failure. [ 9 ] In a prospective 2-year longitudinal study, 237 (32.3%) of 734 patients had AVF stenosis or thrombosis, leading to AVF failure. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…HD-related steal seems to occur more frequently with brachial AVF than with radial or ulnar fistulas. In a systematic review of the Medline literature (from 2000 to 2014, including 43 English-written reports of prospective trials), Al-Jaishi et al [34] concluded that the median complication rate of steal events per 1000 patient days was 0.05. The authors acknowledged that the risk of bias was high and event rates were highly variable, partly due to poor quality studies, significant heterogeneity of study populations and inconsistent definitions of ‘steal syndrome’.…”
Section: Haemodynamic Impacts Of High-flow Avf In Patients Under Chromentioning
confidence: 99%